2017
DOI: 10.18276/cej.2017.2-10
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Physical Activity in Adults Measured by Accelerometer in Compliance with Selected Health Recommendations

Abstract: The aim of the present study was the evaluation of habitual physical activity in adult members of health promoting associations in compliance with selected health recommendations. Physical activity was monitored for 7 consecutive days using accelerometer ActiGraph GT3X+. It was observed that the percentages of individuals with sufficient physical activity differ depending on healthoriented recommendation used in the evaluation. The results indicated that despite appropriate weekly volume of physical activity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The respondents' declared physical activity was also compared with the results of a survey of people from a health promotion association in the Dąbrowa Basin, Poland. This group claimed to undertake moderate-intensity physical activity for 138 minutes per week, while high-intensity efforts for 102 minutes per week [31]. Again, more favorable results were seen in those from ICCs.…”
Section: Discussionmentioning
confidence: 93%
“…The respondents' declared physical activity was also compared with the results of a survey of people from a health promotion association in the Dąbrowa Basin, Poland. This group claimed to undertake moderate-intensity physical activity for 138 minutes per week, while high-intensity efforts for 102 minutes per week [31]. Again, more favorable results were seen in those from ICCs.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, the most frequently evaluated were the compliance with pro-health recommendations based on aerobic (endurance) and mixed effort exercises [36,37,15,38,39,40]. For instance, Scheers and others [38] demonstrated that the WHO recommended weekly volume of physical activity of moderate intensity (150 min.…”
Section: Health Prob Civil 2019 Volume 13 Issuementioning
confidence: 99%
“…To conclude, it is important to emphasise that the studied women met both evaluated criteria of prohealth physical activity, which should be considered a fundamental value of strength training. The results of the research conducted so far indicate that the percentage of respondents meeting specific recommendations decreases with the number of criteria included in them [36,35,38,40].…”
mentioning
confidence: 98%